(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
This study aims to assess the level of Job burnout among the Teaching and Non-Teaching personnel in Zamboanga national high School –West and the effect to the Job performance. The researcher used a Cross-Sectional research design utilizing Descriptive and Correlation Analysis. The study was applied to the to a random sample of (121) personnel, who were chosen through a stratified sampling method, with (31) males and (90) female. A job burnout questionnaire was adopted from Burnout Inventory Index (Maslach,1996), and its validity and reliability were verified. The study’s results of the study showed that the mean of the job burnout of the total degree came with a moderate degree and outstanding job performance. The results also showed that there were no statistically significant differences in the level of job burnout of the total degree attributed to the gender variable and in favor of females. There is a significant difference in the level of job burnout attributed to age, years of service and job description. Moreover, there is no significant relationship in the level of job burnout and job performance on teaching and non-teaching personnel. To the future researcher conduct thorough investigation on the causes of teaching and non-teaching personnel burnout. Additional variable to be investigated such as what curriculum grade level had a highest level of job burnout.